Avetis Grigoryan, Arsen Bobokhian “The Zod”Operation: How Armenia Preserved the Frontier of Sotk in 1919, Yerevan, Newmag, 2022, p. 404 - Virabyan, Vanik (History and Culture, 2022)
One of the most important episodes in Armenian history, “The Zod” operation in 1919, is presented in the review. The authors are Avetis Grigoryan and Arsen Bobokyan. The work is about the forgotten pages of the First Republic of Armenia, related to Zod-Sotk, which are undoubtedly one of the brightest episodes in the annals of the Armenian history of the 20th century.